Ablation Index‐guided high‐power (50 W) short‐duration for left atrial anterior and roofline ablation: Feasibility, procedural data, and lesion analysis (AI High‐Power Linear Ablation). (8th March 2021) - Zanchi, Simone; Chen, Shaojie; Bordignon, Stefano; Bianchini, Lorenzo; Tohoku, Shota; Bologna, Fabrizio; Tondo, Claudio; Chun, K. R. Julian; Schmidt, Boris
Abstract: Objectives: To evaluate the feasibility, procedural data, and lesion characteristics of the anterior line (AL) and roofline (RL) ablation by using ablation index (AI)‐guided high power (50 W) among patients with recurrent atrial fibrillation (AF) or atrial tachycardia (AT) after pulmonary vein isolation (PVI). Methods: Data from 35 consecutive patients with macro‐reentrant left atrial tachycardia or substrate at the left atrium anterior wall or roof after previous PVI were collected. Ablation power was set to 50 W, targeting AI 500 for AL and 400 for RL. The first‐pass conduction block (FPB) was evaluated. The AL was arbitrarily divided into three (caudal, middle, and cranial) segments to analyze the location of conduction gaps in non‐FPB patients. Results: A total of 32 AL and 17 RL were deployed and FPB was achieved in 24 (75%) and 14 (82%) of them, respectively. In the non‐FPB group, the most frequent gap location along the AL was the middle third. The final block of AL was achieved in 97%, and the block of RL was achieved in 100%. The radiofrequency (RF) ablation time was short (2.9 ± 0.8 min for AL and 46.2 ± 15.6 s for RL). For AL, the female gender was significantly more frequent in FPB than in non‐FPB patients ( p  = .028); patients with non‐FPB were associated with significantly longer RF time as compared to patients with FPB (204 ± 47 s vs. 161 ± 41 s; p  = .02). No procedural complications occurred. Conclusion: AI‐guided high‐power (50 W) ablation appears to be a feasible, effective, and fast technique for AL and RL ablation.